Perancangan Project Stakeholder Management Plan Pada Proyek Perluasan Pabrik di PT XYZ - Dhiaulhaq, Ahmad Shidqi; Puspita, Ika Arum; Permatasari, Intan (Innovative: Journal Of Social Science Research, 2024)
This study aims to design a project stakeholder management plan for a factory expansion project at PT XYZ with a focus on stakeholder identification, stakeholder management plan design, and communications management plan design. This study uses PMBOK 6th Edition as the main reference in designing a stakeholder engagement plan and communications management plan. The methods applied include power/interest grid, salience model, stakeholder engagement assessment matrix, and expert judgment. The application of this method allows for the preparation of a more structured and targeted strategy in managing relationships and communications with various stakeholders involved in the project. Based on this study, the results of this design were found in the form of a stakeholder engagement plan and communications management plan developed with a specific engagement strategy and a communications plan tailored to project needs. This design aims to ensure that stakeholder management and communications in the project can run more effectively and efficiently.